2017
DOI: 10.1002/marc.201700396
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Initiators as Tools to Track Chain Transfer during the CROP of 2‐Oxazolines

Abstract: Detailed kinetic studies during the cationic ring-opening polymerization (CROP) of 2-ethyl-2-oxazoline (EtOx) are conducted using four bifunctional bromo-type initiators in N,N-dimethylformamide (DMF) at 140 °C. Serving as models to quantify chain transfer to monomer occurring during the CROP initiated by monofunctional initiators, size exclusion chromatography (SEC) resolves a second molar mass distribution with lower molar mass at initial [monomer] to [initiation site] ratios ([M] /[I] ) of 25, while the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Any detected minor m/z species did not result from the post polymerization modification reactions at the new central unit but were rather caused by commonly observed CROP side reactions such as proton initiation through chain‐transfer as evident already in P1 . [ 26 ] Additional tandem MS investigations clearly confirmed that (see the Supporting Information).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Any detected minor m/z species did not result from the post polymerization modification reactions at the new central unit but were rather caused by commonly observed CROP side reactions such as proton initiation through chain‐transfer as evident already in P1 . [ 26 ] Additional tandem MS investigations clearly confirmed that (see the Supporting Information).…”
Section: Resultssupporting
confidence: 58%
“…Although benzyl bromides are applicable in the CROP of 2‐oxazolines, these attempts resulted in broad molar mass distributions, most likely due to a slow initiation, as has previously been observed for similar initiators. [ 25,26 ]…”
Section: Resultsmentioning
confidence: 99%
“…This behavior has its origins in the ejection dynamics which depend on the 3D structure. As already discussed in literature, when the 3D structure changes, the ejection dynamics change [48] (DP [22][23][24][25][26][27][28][29][30][31][32], leading to the correlation between the observed MS/ MS and IM-MS behaviors.…”
Section: Crossing Ms/ms and Im-ms Informationmentioning
confidence: 99%
“…The increasing compositional and architectural complexity of PAOx and other synthetic polymers developed for advanced applications is giving rise to analytical challenges as the conventional techniques fall short of providing a complete description of the polymer structure (e.g., co-monomer sequence, polymer topologies and branching, isomer identification). PAOx have been the subject of a number of in-depth analytical studies involving mass spectrometry, shedding light on fragmentation pathways [23][24][25], polymerization mechanism [26,27], and unveiling chain transfer reactions [28,29] or the mechanisms associated with polymer degradation [30].…”
Section: Introductionmentioning
confidence: 99%
“…MALDI ToF MS of the TEGTos‐initiated PEtOx (Figures S28 and S29, Supporting Information) revealed various polymer species: The desired polymer species albeit proton‐initiated species and their resulting species due to the α‐elimination of the proton . The POctOx was not measurable by MALDI ToF MS due to the high molar mass of 11 600 g mol −1 .…”
mentioning
confidence: 99%